THE CONCEPTS OF ECONOMIC INFRASTRUCTURE AND SOCIAL INFRASTRUCTURE DEVELOPMENT IN INDIA (International Journal of Food and Nutritional Sciences, 2022)
The present study explained the term ‘infrastructure’ in detail, including the types of infrastructure such as economic infrastructure and social infrastructure. Study also described the key characteristics of infrastructure. The key objective of this paper is to study the current status of economics infrastructure and social infrastructure development in India, covering both sectors economic as well as social infrastructure. The study concluded that infrastructure services positively impacts on economic development and both infrastructure and economic development are interlinked with each other and having a strong relationship.